Fiscal Decentralization in Times of Financial Crises. (10th August 2017) - Bartolini, David; Sacchi, Agnese; Salotti, Simone; Santolini, Raffaella
Abstract: The virtues of fiscal decentralization are usually assessed against the provision of local public goods; little is said about its impact on public finances. There is a growing concern that public finances may be negatively affected when spending and taxing powers are delegated to subnational tiers of government, especially under adverse financial conditions. Our work proves that these concerns are unfounded. The empirical investigation on 19 Organisation for Economic Co-operation and Development countries over the period 1980–2010 shows that the budget balances of central and local governments do not get worse with fiscal decentralization. Moreover, during banking crises expenditure decentralization seems to be beneficial, as the central government can easily shift resources from intergovernmental grants to financing public policies necessary to tackle the crisis. In turn, more subnational tax autonomy would improve the budget of all tiers of government, suggesting that more 'effective' tax decentralization increases fiscal discipline also in times of financial distress. (JEL codes: H60, H70 and G01).